Pemanfaatan Limbah Kulit Kopi Dan Serbuk Gergaji Di Desa Kalipucang Sebagai Bahan Biobriket - abdillah, nabil zhillan; Sani, Sani (LPPM Universitas Internasional Batam, 2024)
Kalipucang Village's residents generally have professions as cattle breeders, but there are some who are coffee farmers. Coffee skin waste is usually sold directly by coffee farmers at a cheap price, where the coffee skins can actually be processed into biobriquettes and the selling price will increase. Coffee skin has a small water content and high calorific value and can be an alternative fuel product, while sawdust has a carbon chain that plays a role in combustion. The quality of the briquettes is obtained by calculating the right composition ratio so that it will produce high quality calorific value and suit people's needs. The thing that must be considered when making briquettes is determining the right ratio of ingredients to increase the heat of the briquettes and their use. It is hoped that making biobriquettes is relatively easy by processing coffee husk waste and sawdust and can become a business idea and for consumption by the Kalipucang community in everyday life.